Sustainable Community Development: Dilemma of Options in Kenya - Waswa, Fuchaka; Kilalo, Christine Ruth Saru.; Mwasaru, Dominic Mwambi; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
Community development has lately gained much prominence, but the emphasis has remained on the economic and social welfare of communities, rather than the environment. By focusing on 'sustainable' development in Kenya, this study shows the importance of integrating ecological concerns in socio-economic and cultural development processes.
Keywords: Africa-History.; Ethnology-Africa.; Sociology, Urban; History, Modern; African History; African Culture; Sociology, general; Urban Studies/Sociology.; Modern History